2019
DOI: 10.1002/ccd.28387
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome in patients treated with first‐ versus second‐generation drug‐eluting stents for the treatment of unprotected left main coronary artery stenosis

Abstract: Objective and background The study aim is to provide long‐term clinical outcome after percutaneous coronary intervention (PCI) for unprotected left main coronary arteries (ULMCA) stenosis with the first‐generation (1st‐gen) drug‐eluting stents (DES) in comparison to 2nd‐gen DES, since this is largely unknown. Methods Between May 2002, and December 2014, a consecutive series of 656 all‐comer patients underwent a PCI for ULMCA stenosis at the Erasmus Medical Center. A total of 235 patients were treated with 1st‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“…Available studies report a 5‐year MACE rate of 34.4% (n=383, age 72.3±9.7 years) 20 and 38.6% (n=421, age 68.4±11.5 years). 21 A large study (n=11 264) reported a 1‐year death rate of 11.5%. 9 Lee et al observed a 3‐year MACCE rate of 16.0% in 1658 individuals treated with new‐generation stents.…”
Section: Discussionmentioning
confidence: 99%
“…Available studies report a 5‐year MACE rate of 34.4% (n=383, age 72.3±9.7 years) 20 and 38.6% (n=421, age 68.4±11.5 years). 21 A large study (n=11 264) reported a 1‐year death rate of 11.5%. 9 Lee et al observed a 3‐year MACCE rate of 16.0% in 1658 individuals treated with new‐generation stents.…”
Section: Discussionmentioning
confidence: 99%
“…По данным 3-[10] и 5-летнего [11] наблюдения, по сравнению со стентами I поколения применение стентов II поколения ассоциировалось с меньшей частотой повторной реваскуляризации целевых поражений. Однако по данным 5-летнего наблюдения [12], группы пациентов со стентированием ствола левой коронарной артерии и имплантированными стентами I и II поколений не различались по частоте повторной реваскуляризации целевого поражения, частоте развития тяжелых сердечно-сосудистых осложнений. По данным 5-летнего наблюдения, необходимость повторной реваскуляризации целевого поражения после имплантации стентов I поколения, содержащих сиролимус, в течение первого года наблюдения была низкой, однако при дальнейшем наблюдении частота повторной реваскуляризации целевого поражения не снижалась [13].…”
Section: Discussionunclassified
“…Several comparative studies of first- and second-generation stents have been carried out. For example, the SPIRIT II clinical study compared the Taxus Express stents with the Xience V (everolimus) drug-eluting stents. After six months, the Xience V had a late loss of lumen (difference in millimeters between the diameter of a stented segment after the procedure compared to the follow-up angiogram at six or nine months) of 0.11 mm compared to 0.36 mm in the Taxus Express, thereby reducing the probability of developing restenosis and a myocardial infarction. , …”
Section: Drugs For the Treatment Of Restenotic And Thrombotic Conditionsmentioning
confidence: 99%